Four new species of Crinopseudoa (Araneae: Corinnidae) from West Africa - Pett, Brogan L.; Pashkevich, Michael D.; Freeman, Benedictus; Timperley, Jonathan H.; Jocqué, Rudy (Zootaxa, 2024)
Four new species of Crinopseudoa are described from West Africa. Crinopseudoa kru sp. nov. (male, female) and C. sinoensis sp. nov. (male, female) were collected as part of a new sustainable oil palm project in southern Liberia, C. nimba sp. nov. (male, female) from expeditions to Mount Nimba in Guinea, and C. elisabethae sp. nov. (male) from historic museum material from Ivory Coast. An updated key to species is presented as we increase the number of known species of Crinopseudoa from 11 to 15.